Mentoring and Networking for Innovation in the school ecosystem: from enabling conditions to MentorQ Self – Evaluation Tool - Giuseppina Rita Jose Mangione; Silvia Panzavolta; Francesca Rossi (Je-LKS: Journal of E-Learning and Knowledge Society)
This study explores the potential of mentoring as a key lever for fostering innovation and systemic improvement in education, focusing on school-to-school mentoring models and the enabling factors that influence their sustainability and effectiveness. Using a mixed-methods approach combining exploratory and confirmatory research, the study identifies ten key enabling factors essential for the success of mentoring practices. These include shared objectives, the comparison of practices, access to resources, and the enhancement of professional skills among stakeholders. Special emphasis is placed on the "hub-and-spoke" model, which has demonstrated effectiveness in promoting collaboration and disseminating innovative practices while adapting to local contexts. Based on the findings, a self-assessment tool, MentorQ, has been developed to support schools in systematically evaluating their mentoring practices, identifying areas for improvement, and strengthening their processes. MentorQ will be piloted within INDIRE's innovation networks, such as Avanguardie Educative and Piccole Scuole, enabling the evaluation of its adaptability across both standardized and non-standardized educational environments. The results underscore the importance of investing in professional development, fostering a collaborative culture, and enhancing the capacity of schools to engage in effective mentoring practices. Future research will focus on validating MentorQ in diverse contexts and further developing a mentoring toolkit, including operational resources and case studies. This work contributes to building sustainable and inclusive mentoring networks, offering concrete tools and insights for driving continuous improvement and innovation in education.